Albania and the Iranian terror threat - Shay, Shaul (Array, 2020)
The national security of countries and the security of the international system are the cornerstones for the stability and prosperity of the international system. Terrorism in general and state-supported terrorism in particular pose a major threat to the security and stability of the international system. In the course of almost 40 years Iran is the world’s leading state sponsor of terrorism and has a long and bloody history of terror attacks. Since 2017 the Iranian regime’s terrorist activities appear to be on the rise on European soil. The Iranian regime appears committed to a strategy of targeting Iranian decedents and Western and Israeli interests, even in Europe. Albania, a close US ally has found itself on the frontline of the clash between the West and Iran and Albania has been at the center of terrorist activities organized by Iran, due to hosting the Mujahideen-e-Khalq (MEK).